Construction of chlorine doped graphitic carbon nitride nanodisc for enhanced photocatalytic activity and mechanism insight. (1st May 2022) - Liu, Wenliang; Wen, Fushan; Wang, Jiqian
Abstract: The development of high-performance doped graphite carbon nitride (g-C3 N4 ) by one-step method has always been potential and yet demanding. Here, we designed a novel Cl doped nanodisc structure g-C3 N4 (Cl(CN)) by one step HCl treatment, without calcination and adding any precursors during the preparation procedure. The photocatalytic activities of samples were assessed toward the hydrogen (H2 ) generation and degradation of rhodamine B (RhB) under simulated solar irradiation, of which the hydrogen production efficiency and degradation efficiency of Cl(CN) were 4 folds and 2.18 folds that of g-C3 N4 (CN), respectively. The overwhelming photocatalytic performance of Cl(CN) was attributed to the synergy effect between the unique nanodisc morphology with high surface area and the regulation of the band structure by the Cl element. To exclude the effect of protonation, the CH3 COOH, H2 SO4, HNO3, KCl, NaCl and NH4 Cl treatments were introduced to compare with HCl treatment. The position of doped Cl and its influence on the band gap as well as electronic structure over g-C3 N4 were investigated by the density functional theory (DFT). In addition, the photocatalytic mechanism of as-prepared samples was further investigated and discussed in detail. This work provided a green and facile protocol for highly active and reusable g-C3 N4 that can address the environmental issuers and energy challenges. Graphical abstract: Image 1 Highlights: A novel Cl(CN) with unique nanodisc structure was obtained by HCl treatment. The Cl(CN) showed superb catalytic ability in H2 production and RhB degradation. The influence of doping Cl over g-C3 N4 was obtained by the DFT calculation. This work offered a potential strategy for improving the activity of g-C3 N4 .